SWOT strategy for future global health security: insights from Indonesia, Cambodia, Vietnam, Dominican Republic, Ghana, and the Republic of Korea using the World Health Organization International Health Regulations monitoring tool - Moonsoo Yoon; Nuha Fairusya; Thao Le Nhu Nguyen; Diomarys Ishaura Jimenez-Baez; Vichuta Prak; Osei Kuffour Afreh; Chaeshin Chu (Osong Public Health and Research Perspectives)
Objectives The study aimed to analyze the core capacities to implement World Health Organization International Health Regulations (IHR) in 6 countries: Indonesia, Cambodia, Vietnam, the Dominican Republic, Ghana, and the Republic of Korea. Methods Secondary data from relevant databases and reports, including the electronic State Party Self-Assessment Annual Reporting mechanism and global health security index, were used to assess health security in these countries. Descriptive statistics summarized the basic features of the scores, and a strengths, weaknesses, opportunities, and threats (SWOT) analysis was subsequently performed to identify factors affecting health security scores while highlighting key similarities and differences between countries. Results Early warning and event management emerged as the primary strength in most countries. Common opportunities included international commitments and immunization programs. In contrast, many countries shared weaknesses related to the policy, legal, and normative frameworks for IHR implementation, as well as challenges in human resources, chemical event management, and radiation emergency preparedness. Recurring threats involved issues such as biosafety, biosecurity, dual-use research and the culture of responsible science, infection control practices, coordination between public health and security authorities, laboratory supply chain vulnerabilities, and communication with healthcare workers during public health emergencies. Conclusion In order to counter future global health threats, countries should prioritize enhancing surveillance capacity (early warning and event management) as well as the immunization indicator (vaccination rates for human and animal diseases, including the national vaccine delivery system).